2007
DOI: 10.1249/mss.0b013e3180601136
|View full text |Cite
|
Sign up to set email alerts
|

Flattening of Oxygen Pulse during Exercise May Detect Extensive Myocardial Ischemia

Abstract: The analysis of the oxygen pulse response to incremental exercise test does not identify mild myocardial ischemia. Flattening of oxygen pulse response during incremental exercise might be present only with extensive myocardial ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 14 publications
0
44
2
2
Order By: Relevance
“…Moreover, symptomatic patients had significantly lower values of the same parameters and a higher reduction of left ventricular ejection fraction at peak effort compared with the silent ischemia group [148]. In another study [149], patients with exercise-induced ischemia presented peakVO 2 and oxygen pulse values similar to those of patients with normal perfusion; however, patients with extensive transient perfusion defects had a lower peak oxygen pulse than those with lower exerciseinduced ischemia. Decreased VAT VO 2 has also been consistently shown to be related to the presence [148][149][150][151][152] and the extent [153] of myocardial ischemia.…”
Section: Circulatory Powermentioning
confidence: 87%
“…Moreover, symptomatic patients had significantly lower values of the same parameters and a higher reduction of left ventricular ejection fraction at peak effort compared with the silent ischemia group [148]. In another study [149], patients with exercise-induced ischemia presented peakVO 2 and oxygen pulse values similar to those of patients with normal perfusion; however, patients with extensive transient perfusion defects had a lower peak oxygen pulse than those with lower exerciseinduced ischemia. Decreased VAT VO 2 has also been consistently shown to be related to the presence [148][149][150][151][152] and the extent [153] of myocardial ischemia.…”
Section: Circulatory Powermentioning
confidence: 87%
“…Even with our effort to minimize the intervening variables as much as possible and thereby increase the external validity of these results, the current study has some limitations: a) because the O 2 pulse is a variable that is mainly used in the clinical environment for prognostic stratification (11) and to detect myocardial ischemia (14), we may speculate that the results obtained from healthy young men having good to excellent aerobic fitness may not be applicable to other populations of greater clinical interest. On the other hand, because the subjects most likely did not present changes in relation to their aerobic training routine during the period of data collection and did not exhibit cardiorespiratory illnesses that could affect the maximum value of their relative O 2 pulse curve, any changes in these variables represent patterns within normal variation and not pathological alterations, which are frequently observed in clinical practice; b) considering the nature of a competitive season in this sports modality, it would not be feasible to precisely control the volume and intensity of aerobic training of these players between the evaluations.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the shape of the O 2 pulse curve during progressively more intense exercise is equally important, since it may be altered in a variety of situations, such as the presence of coronary artery disease (3,13). Therefore, recent evidence has pointed to a role for O 2 pulse data as an important clinical tool to detect severe myocardial ischemia (10,14,15).…”
mentioning
confidence: 99%
“…Since the original report of Belardinelli et al ,6 studies have demonstrated that the trajectory of oxygen pulse provides valuable information for the evaluation of patients with CAD 4 6 10 15 21. Under normal physiological conditions, O 2 pulse progressively rises throughout ET with possible plateau approaching maximal exertion.…”
Section: Discussionmentioning
confidence: 99%
“…It provides greater diagnostic accuracy, additional prognostic information, more precise determination of aerobic capacity and a unique insight into independent and coupled functions of the cardiovascular, pulmonary and skeletal muscle systems 2 3 5–7. Although it has been proposed that information derived from CPET could help with the diagnosis of myocardial ischaemia, it has been of little use in the evaluation of patients with CAD 4 8…”
Section: Introductionmentioning
confidence: 99%